Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.3325/cmj.2009.50.380
|View full text |Cite
|
Sign up to set email alerts
|

Association of Socioeconomic Status and Life-style Factors with Coping Strategies in Isfahan Healthy Heart Program, Iran

Abstract: Coping strategies of the population in central Iran were highly influenced by socioeconomic status and life-style factors. Programs aimed at improving healthy life-styles and increasing the socioeconomic status could increase adaptive coping skills and decrease maladaptive ones and consequently lead to a more healthy society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 23 publications
2
27
2
4
Order By: Relevance
“…The reported relation of perceived stress and age in most recent previous studies [6, 68] was in contrast with our findings. This difference may be attributed to socioeconomic status of Iranian society that the young people more faced with high levels of stress due to financial problems and job insecurity.…”
Section: Discussioncontrasting
confidence: 99%
“…The reported relation of perceived stress and age in most recent previous studies [6, 68] was in contrast with our findings. This difference may be attributed to socioeconomic status of Iranian society that the young people more faced with high levels of stress due to financial problems and job insecurity.…”
Section: Discussioncontrasting
confidence: 99%
“…While the infertile women with low educational level used active and passive-avoidance coping strategies significantly more than the women with higher educational level (table 5). This finding may be attributed to the fact that highly educated women are more prone to use problem-focused approaches, such as doing something regarding a problem, outlining the cause, thinking through the situation and looking for (37) research, they did investigate the association of socioeconomic status and life-style factors with coping strategies in Isfahan Healthy Heart Program, Iran. They found that there was a positive relation between high education level and adaptive coping strategies and a negative relation between low education level and mal-adaptive coping strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, the investigators found the significant effects of the education variable on coping strategy, and detected a positive and negative association between the number of education year with adaptive coping strategies and maladaptive coping strategies, respectively; interestingly, the sex variable could modify its effect. In addition, compared to other job positions, they found that manual workers used maladaptive strategies more frequently (30). This difference effect could be the result of the type of studied population.…”
Section: Discussionmentioning
confidence: 83%